2013
DOI: 10.1002/oby.20437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sugar‐sweetened beverages on plasma acylation stimulating protein, leptin and adiponectin: Relationships with Metabolic Outcomes

Abstract: Objective We determined the effects of fructose and glucose consumption on plasma acylation stimulating protein (ASP), adiponectin, and leptin concentrations relative to energy intake, body weight, adiposity, circulating triglycerides, and insulin sensitivity. Design and Methods 32 overweight/obese adults consumed glucose- or fructose-sweetened beverages (25% energy requirement) with their ad libitum diets for 8 weeks, followed by sweetened beverage consumption for 2 weeks with a standardized, energy-balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 42 publications
(48 reference statements)
3
46
0
Order By: Relevance
“…Previous studies have shown that excess sugar consumption is sufficient to decrease serum adiponectin levels in rats [50] and humans [51]. In the present study, we observed that serum adiponectin levels were decreased in mice fed diets containing high sugar.…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies have shown that excess sugar consumption is sufficient to decrease serum adiponectin levels in rats [50] and humans [51]. In the present study, we observed that serum adiponectin levels were decreased in mice fed diets containing high sugar.…”
Section: Discussionsupporting
confidence: 71%
“…Food intake appeared to be similar and weight gain was comparable between the subjects consuming 25% Ereq as fructose- or glucose-sweetened beverages with ad libitum diets for 8 weeks (33). However, in these same subjects, we also observed a fructose-induced decrease in 24-h leptin levels (123), and a decrease in fasting energy expenditure that was not observed with glucose consumption (31). Why then did the subjects consuming fructose fail to show increased body weight gain compared with the subjects consuming glucose?…”
Section: Introductionmentioning
confidence: 54%
“…Leptin production by adipocytes is regulated by insulin-mediated glucose metabolism (121). Ingestion of fructose does not result in meal-related increases of plasma glucose or insulin concentrations, therefore both short (34, 122) and long-term (123) studies demonstrate that meals accompanied with fructose-sweetened beverages result in reduced circulating leptin concentrations compared with glucose-sweetened beverages. Leptin acts, along with insulin, in the hypothalamus to regulate food intake and energy metabolism via neuropeptide systems including neuropeptide-Y and melanocortins.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased adiponectin levels in systemic circulation closely correlates with accumulation of vesical adipose and dysregulation of insulin-stimulated glucose uptake and utilization [154]. Therefore, abdominal and visceral adiposity, reduced insulin-sensitive visceral adipocytes, as well as increased body weight and fat under high fructose feeding [29,155], cause adiponectin secretion reduction [151].…”
Section: Adiponectinmentioning
confidence: 99%